Sikap Petani terhadap Program Toko Tani Indonesia di Kecamatan Margoyoso Kabupaten Pati - Rizqiyah, Meita Fatimatur; Padmaningrum, Dwiningtyas; Wijianto, Arip (Universitas Sebelas Maret, 2020)
TokoTani Indonesia (TTI) is a program that aims to cut the food supply chain so the price disparity between farmers and consumers does not occur and improve farmer’s prosperity. This research aims to describe the farmer attitudes towards TTI Programme at Margoyoso District Pati Regency, individual experience, formal education, and significant others who are considered notable to farmers in TokoTani Indonesia (TTI) Programme, influences from individual experience, non-formal education, and significant others who are considered notable towards farmer’s attitudes regarding TTI programme. This research was conducted in Margoyoso District, Pati Regency. Population of this research are 604 farmers as member of Gapoktan Sido Makmur in Purwodadi Village, Tani Makmur Manunggal in Soneyan Village, and Jaya Makmur in Purwodadi Village. Sampling was determined using proportional random sampling technique of 60 farmers. Data analysis using multiple linear regression with IBM SPSS Statistic 16 program. The results showed farmers disagree with Toko Tani Indonesia (TTI) program; factors that influence farmers attitude are: individual experience was included in negative category, while non- formal education and significant others were included in low category; simultaneously, all independent factors was significantly influence dependent factor, while partially factors was significantly influence are individual experience, non-formal education, and significant others.